Growth Response of Cymbidium Orchid (Cymbidium Finlaysonianum) Subcultures Due to the Addition Naa and Kinetin - Ainaya, Ainaya; Handayani, Rd. Selvy; Nazirah, Laila; Nilahayati, Nilahayati; Faisal, Faisal (Yayasan Pertanian Tropika Indonesia (YPTI), 2022)
The Cymbidium orchid plant is a popular ornamental plant among Indonesians due to its beautiful blooms with unique shapes and colors. The generative propagation of orchid plants cannot be done conventionally.Â This is due to the unavailability of food storage (endosperm)in the orchid plant. The purpose of this research was to determine the effect of NAA and kinetin on the growth of Cymbidium finlaysonianum orchid subcultures in vitro. The research method used was a factorial Completely Randomized Design (CRD) that consists of two factors which are the concentration of Naphthalene Acetic Acid (NAA) (0 mg/L, 0,5 mg/L, 1 mg/L) and kinetin (0 mg/L, 1 mg/L, 2 mg/L). The results showed that NAA can reduce the growth of Cymbidium orchid subcultures on the number of buds 7-8 WAP and root growth time. The best treatment is found in the treatment of 0 mg/L of NAA. 2. Kinetin can increase the growth of Cymbidium orchid subcultures up to a concentration of 1 mg/L at the percentage of root growth 5 WAP and the number of roots 5-7 WAP. The best treatment is found in the 1 mg/L of Kinetin. 3. The interaction between the concentration of NAA and Kinetin only affects the number of shoots 3-4 WAP and the number of roots at the age of 6-8 WAP. The best treatment was 0 mg/L of NAA + 1 mg/L of Kinetin.